KRITIK MU’TAZILAH TERHADAP SISTEM FILSAFAT IBN SINA: ANALISIS PEMIKIRAN TAKLIF IBN AL-MALAHIMI - Rakhmat, Aulia (UIN Sunan Kalijaga Yogyakarta, 2022)
The Mu'tazilites were considered to have close relationship with Muslim philosophers and because of this, many thought that the two had share poin of vies. However, this is not always the case. There are philosophical teachings that contradict to concept of Mu'tazilite theology. This gave birth to a theological critique of the Mu'tazilite against philosophy. Therefore, this article attempts to analyze the Mu'tazilah criticism of Ibn Sina's philosophical system focusing on the study of Ibn al-Malahimi's analysis of taklif written in his book intended to criticize philosophy, Tuhfat al-Mutakallimin fi al-Radd 'ala al-Falasifa. There are two reasons for studying the issue of taklif: first, the concept of taklif is the central doctrine of the Mu'tazilah because it relates to important concepts such as rewards and punishments, prophetic purposes and human actions. Therefore, it is important to study the Mu'tazilite criticism leveled at Ibn Sina on the issue of taklif. Second, the discussion about taklif is not found in the 20 points of criticism raised by al-Ghazali in his Tahafut Falasifah and therefore it can provide valuable insight of the theologian's assessment of the philosopher. This paper argues that Ibn al-Malahimi's purpose to present Ibn Sina's thoughts in the realm of taklif is his strategy to expose Ibn Sina's thoughts that are contrary to the Mu'tazilah doctrine. Through the discussion of taklif, Ibn al-Malahimi can uncover several interrelated issues such as the purpose of prophethood, the concept of reward and punishment and most importantly, reveal the deterministic understanding of human action held by Ibn Sina and his followers.